Konstitusionalisme dan Konstitusi Ditinjau dari Perspektif Sejarah - Effendi, Syafnil (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2011)
The primary mission of constitutionalist thought is the limitation of power of the government. This limitation means the guarantee and protection of rights of the society. The thought about the limitation of government power aims to avoid power abuse, authoritarian and irresponsible acts. In the constitutional democratic countries, constitutionalism is one of qualifications of democratic countries. However, the democracy is questioned when constitutionalism is included in the constitution and in the real implementation of the state. Key words: constitutionalism, constitution